Bone health in Parkinson's disease: a systematic review and meta-analysis. Issue 10 (11th March 2014) - Torsney, Kelli M; Noyce, Alastair J; Doherty, Karen M; Bestwick, Jonathan P; Dobson, Ruth; Lees, Andrew J
Abstract : Objective: Parkinson's disease (PD) and osteoporosis are chronic diseases associated with increasing age. Single studies have reported associations between them and the major consequence, namely, increased risk of fractures. The aim of this systematic review and meta-analysis was to evaluate the relationship of PD with osteoporosis, bone mineral density (BMD) and fracture risk. Methods: A literature search was undertaken on 4 September 2012 using multiple indexing databases and relevant search terms. Articles were screened for suitability and data extracted where studies met inclusion criteria and were of sufficient quality. Data were combined using standard meta-analysis methods. Results: 23 studies were used in the final analysis. PD patients were at higher risk of osteoporosis (OR 2.61; 95% CI 1.69 to 4.03) compared with healthy controls. Male patients had a lower risk for osteoporosis and osteopenia than female patients (OR 0.45; 95% CI 0.29 to 0.68). PD patients had lower hip, lumbar spine and femoral neck BMD levels compared with healthy controls; mean difference, −0.08, 95% CI −0.13 to −0.02 for femoral neck; −0.09, 95% CI −0.15 to −0.03 for lumbar spine; and −0.05, 95% CI −0.07 to −0.03 for total hip. PD patients were also at increased risk of fractures (OR 2.28; 95% CI 1.83 to 2.83). Conclusions: This systematic review and meta-analysis demonstrate that PD patients are at higher risk for both osteoporosis and osteopenia compared with healthy controls, and that female patients are at greater risk than male patients. Patients with PD also have lower BMD and are at increased risk of fractures.